Properties of Full Jet in High-Energy Heavy-Ion Collisions from Parton Scatterings - Guo-Liang Ma; Mao-Wu Nie (Advances in High Energy Physics)
The properties of fully reconstructed jet are investigated in p + p and Pb + Pb collisions at sNN = 2.76 TeV within a multiphase transport (AMPT) model with both partonic scatterings and hadronic rescatterings. A large transverse momentum (pT) asymmetry of dijet or photon-jet arises from the strong interactions between jet and partonic matter. The ξ-dependent jet fragmentation function in Pb + Pb collisions is decomposed into two contributions from different jet hadronization mechanisms, that is, fragmentation versus coalescence. The medium modification of differential jet shape displays that the jet energy is redistributed towards a larger radius owing to jet-medium interactions in heavy-ion collisions. Jet triangular azimuthal anisotropy coefficient, v3jet, which shows a smaller magnitude than the elliptic coefficient v2jet, decreases more quickly with increasing jet pT, which can be attributed to a path-length effect of jet energy loss. All of these properties of full jet are consistent with the jet energy loss mechanism in a stronglyinteracting partonic matter in high-energy heavy-ion collisions.